Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/ibd/izab152
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress in Patients With Inflammatory Bowel Disease: Prevalence and Relationships to Patient-Reported Outcomes

Abstract: Background Patients with chronic illness are at increased risk for traumatic stress because of medical trauma. Initial studies of posttraumatic stress (PTS) in patients with inflammatory bowel disease (IBD) have found that approximately one-third of patients may experience significant PTS symptoms including flashbacks, nightmares, hypervigilance, disrupted sleep, and low mood. We aim to better characterize PTS in IBD and its relationship with patient outcomes in a large cohort of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
3
21
2
Order By: Relevance
“…This is the first study investigating the prevalence of both IBD-related PTSD and dissociative symptoms in a cohort of patients compared to healthy controls. According to recent studies, IBD patients are more susceptible to PTSD symptoms compared to patients with irritable bowel syndrome [18], and this psychological comorbidity could play a negative impact on IBD outcomes [19]. Our results, from an Italian IBD outpatients setting, confirm the high prevalence of IBD-related PTSD, as recently shown by a US study [19], and expand this observation by adding information on the high prevalence of IBD-related dissociative symptoms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is the first study investigating the prevalence of both IBD-related PTSD and dissociative symptoms in a cohort of patients compared to healthy controls. According to recent studies, IBD patients are more susceptible to PTSD symptoms compared to patients with irritable bowel syndrome [18], and this psychological comorbidity could play a negative impact on IBD outcomes [19]. Our results, from an Italian IBD outpatients setting, confirm the high prevalence of IBD-related PTSD, as recently shown by a US study [19], and expand this observation by adding information on the high prevalence of IBD-related dissociative symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…The rationale for this association could be represented by bidirectional gut-brain interactions and systemic inflammation [17] and supported by the association between PTSD and CD activity [16], as well as by the higher prevalence of PTSD among IBD compared to IBS patients [18]. In addition, PTSD seems to be associated with several IBD outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that IBD patients with an underlying robust indication for stoma surgery, either persistence of stoma or stoma closure surgery, do not appear to have a sustainably impact future psychological wellbeing. This contradicts previous studies indicating surgery to be a trigger for PTSD [22] and showing that patients with higher PTSD symptoms have more likely had surgery [46]. This correlates with the finding that patients in the SIBDCS with ostomy scored higher in the PDS total score, showed a higher avoidance of stimuli associated with ostomy and a higher re-experiencing score in the SIBDCS.…”
Section: Discussioncontrasting
confidence: 56%
“…This correlates with the finding that patients in the SIBDCS with ostomy scored higher in the PDS total score, showed a higher avoidance of stimuli associated with ostomy and a higher re-experiencing score in the SIBDCS. This could however also be due to a relatively more severe course of disease (stoma as a surrogate for a more debilitating disease course, imperfect matching; as mentioned above) which has also been shown to impact severity of PTSD symptoms [46]. It has also to be stressed that none of the studies focused specifically on ostomy and that we were able to show a decrease in PDS avoidance score in patients with permanent ostomy and an increase in closed ostomy, suggesting a possible impact of stoma type (permanent/closed).…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting the bi-directional nature of the brain-gut axis, stress, including post-traumatic stress (PTS) have been identified as a key process influencing digestive processes [7][8][9]. Further, living with a medical condition (such as IBD) is linked to the development of PTS [10][11][12][13], and subsequently, posttraumatic stress disorder (PTSD). In a recent systematic review, Glynn et al [14] identified that the prevalence of PTSD across gastrointestinal cohorts was high, with 31% of individuals with inflammatory conditions (e.g., ulcerative colitis, Crohn's disease, gastro-oesophageal reflux disease, peptic disease) having PTSD.…”
Section: Introductionmentioning
confidence: 99%